Porovnání automobilů s různými zdroji energie - Černý, Metoděj; Metoděj Černý (České vysoké učení technické v Praze, 2022)
Cílem bakalářské práce je zhodnocení provozu automobilů s odlišnými zdroji energie z ekonomického, ekologického a uživatelského hlediska. V první části práce představuji technické parametry zástupců naftového, plynového a elektrického pohonu. Za účelem znázornění modelů provozu vozidel jsem využil referenční rodiny lišící se ročním nájezdem a stylem života. Ekonomická část práce sestává z kalkulace nákladů spojených s provozem a výsledného porovnání na základě kritéria ekonomické efektivnosti NPV a citlivostní analýzy. Součástí práce je rovněž porovnání dopadu jednotlivých subjektů na životní prostředí, kde je posuzována fáze výroby, provozu a likvidace vozidla. Závěrem práce provádím vícekriteriální analýzu, jejichž cílem je popsat a následně zhodnotit možné výhody a nevýhody vozidel.

The aim of the bachelor thesis is to evaluate the operation of cars with different energy sources from the economic, ecological and user point of view. In the first part of the thesis I present the technical parameters of representatives of diesel, gas and electric powertrains. The model of vehicle operation is represented by reference families differing in annual mileage and life style. The economic part of the thesis consists of the calculation of all costs associated with the operation of the vehicles and the resulting comparison based on the NPV criterion and sensitivity analysis. The thesis also includes a comparison of the environmental impact of each entity, where the production, operation and disposal phases of the vehicle are included. Finally, the thesis concludes with a multi-criteria analysis to describe and then evaluate the possible advantages and disadvantages of the vehicles.
Vehicle operation with Dierent Energy Sources Evaluation
Keywords: Spalovací motor; elektromobilita; emise CO2; skleníkové plyny; Škoda Auto; Tesla; trakční baterie; dobíjecí stanice; provozní náklady; CNG; Combustion engine; electromobility; CO2 emissions; greenhouse gases; Skoda Auto; Tesla; traction battery; charging station; operational costs; CNG